2006
DOI: 10.1159/000092515
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Allergy and Extensive Lipoatrophy in Child with Type 1 Diabetes

Abstract: Insulin allergy and lipoatrophy in type 1 diabetic patients have been previously reported but the mechanisms are not well documented. Here, we report a case emphasizing the role of abnormal local immune reaction associated with cytokine hyper production. The patient is a 7-year-old boy with a familial history of common variable immunodeficiency. Eight months after the diagnosis of type 1 diabetes, he developed signs of insulin allergy expressed as continuously extensive and profound lipoatrophy contrasting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…An immunologic reaction in the development of lipoatrophy is strongly suspected. Immunofluorescence analysis of affected skin has shown abnormal accumulation of immunoglobulins and complement in dermal blood vessels initiating a signaling cascade that results in inhibition of adipocyte differentiation 101,102 . The likelihood of lipoatrophy decreases with regular rotation of the infection area.…”
Section: Skin Complications Due To Therapy Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…An immunologic reaction in the development of lipoatrophy is strongly suspected. Immunofluorescence analysis of affected skin has shown abnormal accumulation of immunoglobulins and complement in dermal blood vessels initiating a signaling cascade that results in inhibition of adipocyte differentiation 101,102 . The likelihood of lipoatrophy decreases with regular rotation of the infection area.…”
Section: Skin Complications Due To Therapy Of Diabetesmentioning
confidence: 99%
“…Immunofluorescence analysis of affected skin has shown abnormal accumulation of immunoglobulins and complement in dermal blood vessels initiating a signaling cascade that results in inhibition of adipocyte differentiation. 101,102 The likelihood of lipoatrophy decreases with regular rotation of the infection area. In contrast, lipohypertrophy is characterized by increase of local subcutaneous fat.…”
Section: Cutaneous Reactions To Insulinmentioning
confidence: 99%
“…Geldof et al [61] reported a patient who developed hand eczema associated with CSII. In another paper, Beltrand et al [62] reported a 7-year-old boy who developed insulin allergy and extensive lipoatrophy although his insulin treatment switched to CSII after first signs of insulin allergy had appeared. Durand-Gonzalez et al [63] reported that insulin allergy reappeared 7 weeks after the initiation of CSII in a patient with gestational diabetes who had first developed insulin allergy while using insulin injections.…”
Section: Continuous Subcutaneous Insulin Infusion (Csii)mentioning
confidence: 99%
“…Thus, we hypothesize that the complete absence of endogenous insulin protein in our patient prevented induction of immune tolerance resulting in antibody production against the exogenous insulin followed by progressive immune-mediated lipoatrophy at injection sites. Indeed, Beltrand et al (16) previously suggested that immune insulin-induced lipodystrophy involves the local formation of immune complexes, complement fixation, and release of cytokines. The latter causes a loss of differentiation of subcutaneous fat tissue, the inhibition of the differentiation of adipocyte precursors and the delipidation of mature cells, as described in our patient's pathology report.…”
Section: Discussionmentioning
confidence: 99%